HEALTHCARE APPLICATIONS OF GLUCONIC ACID: A COMPREHENSIVE REVIEW AND INSIGHTS (International Journal of Food and Nutritional Sciences, 2022)
Gluconic acid, a naturally derived compound from glucose oxidation, has gained increasing significance due to its wide range of applications, especially in healthcare. This review traces the evolution of gluconic acid, from its early use in enhancing mineral absorption to its extensive modern-day applications across multiple industries. Its distinctive properties, such as metal ion chelation and antimicrobial activity, make it an essential component in wound healing, drug delivery, and mineral supplements. Beyond healthcare, gluconic acid’s versatility has extended to personal care, agriculture, pharmaceuticals, and construction. The growing demand for sustainable and eco-friendly products has also driven its use in biodegradable cleaning agents, textiles, and water treatment. Despite challenges like high production costs and infrastructure needs, its role in advancing safer, more efficient products remains crucial. As global priorities shift toward health and sustainability, gluconic acid is poised for ongoing growth and innovation. Its capacity to improve nutrient absorption, stabilize pharmaceuticals, and enhance industrial processes underscores its broad value. This review offers a comprehensive look at gluconic acid’s applications, production methods, and market trends, showcasing its potential for future developments in both healthcare and industrial sectors. Additionally, the review highlights gluconic acid's journey from a simple organic compound to a key player in therapeutic applications, emphasizing its role in tissue repair, infection control, and drug stability. Its continued relevance in both conventional and emerging treatments points to a promising future across various industries.